Main patterns of modern river morphodynamics of the Carpathian region - Bayrak, Galyna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
The article describes the morphodynamics of river sections belonging to the foothill and flatland wide-floodplain channel types of the Carpathian region.Purpose: to investigate the types and general patterns of river morphodynamics of the Carpathian region based on different-time cartographic information and remote sensing.Methods: GIS technologies, remote sensing methods, cartographic, comparative, field research. Maps and satellite different time data were geocoded in QGIS software. Maps of the 1870s–1940s from the resource "Archival Maps of Poland and Europe" at scales of 1:75,000 and 1:100,000, topographic maps of the 1950s–1990s at scales of 1:50,000 and 1:100,000, maps from the Open Street Map (2014), satellite data from 2005–2021 from the Google Earth with a resolution of 1 m/pixel and the EO Browser (2024, resolution of 10 m/pixel) were used for analyze the dynamics of riverbeds.Results. Seven morphological types of river channels were identified: single-thread straight channel, single-thread slightly sinuous, single-thread meandering, two-thread straight, two-thread slightly sinuous, multi-thread straight and multi-thread slightly sinuous channels. Changes in these riverbeds types at different times since 19th century were analyzed. All data of the channels morphodynamics were grouped into ten time periods before the extreme floods of 1900, 1927, 1941, 1969, 1980, 1989, 2008, 2014 and 2020, as well as the situation in 2024. The number of channel types was calculated in relation to the total number for a certain period. There were the most common single-thread straight types in 1980–1989; single-thread slightly sinuous forms in 1900–1927 and 2024; single-thread meandering – before 1900 and 2008–2014; two-thread straight and sinuous types – before 1900 and in 1950–1970, and at other times they were even less or absent; multi-thread straight and sinuous types – before 1900 and in the 1970s. Based on the channels morphodynamics analysis, the following types were distinguished: transversal and longitudinal displacements. Transversal types include parallel displacement of channels relative to the floodplain axis, changes from single-thread to double- and multi-thread channels, expansion of the meander radius, 180-degree turn of meander, changes of meander types, extinction of threads in braided channels. Longitudinal displacements types are as follows: changes in the length of the meandering zone, meanders displacement downstream, changes in the meanders necks and tops, river branches displacement downstream.Scientific novelty. It was shown that river segments changing laterally return to their original shape over a certain period, and it is a cycle of changes in riverbed sections. The largest number of change cycles was studied for single-thread channels, and four cycles were identified for it. Two cycles were identified for braided channels.Practical significance. The study of the river morphodynamics and its cyclity will allow solving the problems of predicting these changes and preventing the negative impacts of dangerous phenomena associated with river floods. Taking into account of the river morphodynamics features is important for planning of the floodplains and low terraces development, designing safe and stable buildings that will't be damaged by channel changes.